MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DENGAN METODE IMPROVE DISERTAI PEMBERIAN EMBEDDED TEST DI SEKOLAH MENENGAH KEJURUAN - Dasit, Dominikus; Suratman, Dede; Yani, Ahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract The purpose of this research is to know the students' mathematical problem solving ability during the process, after the process, and also the improvement of problem solving ability of students before and after process and the students? activities during learning process by IMPROVE method along with embedded test in arithmetic sequence. In order to achieve this goal, an effort is made to improve the quality of education through learning methods and it is possible if their potential is sharpened with problem solving ability so they are used to think critically, logically and creatively. The design used is Pretest and Posttest Group and it is used in one group only, so it does not need a control group. The population is the X grade students at SMK Negeri I Ngabang in academic year 2017-2018, one sample class is taken from Accounting B class which will be treated with IMPROVE method with embedded test.The results of the research showed the students' mathematical problem solving ability using IMPROVE method along with the embedded test during and after the process increased, the final score reached the Minimum Mastery Criteria (KKM) and the students activity increased. Keywords: Improve method, embedded test, solving problem ability.